Pulpit - Ghosh, Ayan (2023)
The original pulpit at St. Thomas Church was made of stone. The current pulpit is made of green Italian marble made by sculptors in Italy. It was donated by AK Leslie and his wife, Grace Emily Leslie, in loving memory of Emily's father, Sir George Cotton. The three figures on the pulpit are allegorical representations of Faith, Hope, and Charity.